50.9k views
2 votes
Prove csc (pi/2 - x) = sec x

Prove csc (pi/2 - x) = sec x-example-1
User JanithaR
by
5.4k points

2 Answers

6 votes

Hello!

The correct answer is: D.
cscx((\pi )/(2)-x)=(1)/(sin(\pi )/(2) *cosx-cos(\pi )/(2) *sinx)=secx

Why?

Let's put a letter to each option in order to make the explanation easier:

First option will be A

Second option will be B

Third option will be C

Fourth option will be D

So,

First we need to know that:


cscx=(1)/(sinx)

and


sin(x-y)=sinx*cosy-cosx*siny

Therefore:


secx=(1)/(sin((\pi )/(2)-x) )=(1)/(sin(\pi )/(2) *cosx-cos(\pi )/(2) *sinx)=secx


secx=(1)/(1*cosx-0 *sinx)=(1)/(cosx)=secx

Then,


secx=secx=cscx((\pi )/(2)-x)

Have a nice day!

User Jenish
by
5.0k points
5 votes

Answer:

The answer is the last one ⇒
csc((\pi )/(2)-x)=(1)/(sin(\pi )/(2)cosx-cos(\pi )/(2)sinx  )

Explanation:

∵ sin(π/2 - x) = sinπ/2 cosx - cosπ/2 sinx

∵ sin(π/2) = 1 , ∵ cos(π/2) = 0

∴ sin(π/2 - x) = (1) × cosx - (0) sinx = cosx

∵ csc(π/2 - x) =
(1)/(sin(\pi )/(2)-x )

∴ csc(π/2 - x) = 1/cosx = secx

User BigTime
by
4.9k points